PENGEMBANGAN BAHAN AJAR MEMBACA PERMULAAN DALAM PEMBELAJARAN TEMATIK DENGAN MODEL VARK (VISUAL, AUDITORY, READ/WRITE AND KINESTHETIC) DI KELAS I SEKOLAH DASAR - Maistika Ratih; Taufina Taufina (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Malang, 2019)
This study aims to produce the process of developing teaching reading materials and produce teaching reading materials with Vark (Visual, Auditory, Read / write, and Kinesthetic) models for class 1 valid and practical educators and students. The development is based on the Plomp model (Preliminary Research, Prototyping Phase and Assessment Stage) which emphasizes the context of needs (educators and students) so that the initial reading skills learning material is produced based on the Vark model. Based on the results of the Kevalitan trial, it can be seen from the validation of content, language, presentation, graphics and lesson plans, overall 93.10% with valid valid categories. Praticality of teaching materials is seen from the educator's response, 98.92% of the students' responses are 96.15% while the effectiveness of Reading is a percentage of 100%. It can be concluded that the preliminary reading material using the Vark model that was developed is suitable for use in reading the beginning with the Vark model in grade 1 elementary school.